A Way of Thinking about Collective Bargaining: Circumstance, Policy, Law and Actuality - Carrothers, A.W.R. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1985)
The object of this paper is to offer a taxonomy — a kind of classification System — as an aid to thinking, in a number of interrelated dimensions, about collective bargaining as a phenomenon of the relationship between management and labour.